Internet banking adoption in a developing country – an empirical study. (1st January 2013) - Varaprasad, G.; Sridharan, R.; Anandakuttan B., Unnithan
The progressions in information technology have changed the operational aspects of the banking sector significantly. Internet banking has been found to be an alternative channel for the traditional banking as it saves time, money and effort. The objective of this study is to identify the prominent factors that influence the public sector bank consumers in India to adopt internet banking services. Factors such as perceived usefulness, perceived ease of use, perceived risk, relative advantage and trialability have been found to be the determinants of internet banking in the previous studies. Along with the above variables a new variable called conspicuousness has been analysed in the present study. This kind of study has not been conducted in the Indian context previously. A model has been proposed and tested using linear multiple regression analysis. The findings are of great use primarily for the banks which are planning to offer internet banking services, and for already existing banks to focus on the gaps.